Toward a Defined Role for Occupational Therapy in Foster Care Transition Programming - Armstrong-Heimsoth, Amy (Open J Occup Ther, 2020)
Youth who age out of the foster care system and transition to adulthood face challenges that are exacerbated by a history of trauma, severed relationships, and instability of living and educational placements. A review of the literature demonstrates poor outcomes overall for this population. Occupational therapists are positioned to meet the needs that arise during this time; however, a review of emerging roles for occupational therapists is necessary to describe how occupational therapists can best fulfill gaps in current programming. Through a review of the literature and a preliminary mixed-methods study, this paper establishes a direction for the inclusion of occupational therapy for youth aging out of foster care using the Person Environment Occupation Performance (PEOP) model as a structure. Federal, state, and local organizations provide resources to assist transitioning foster youth. However, there is a lack of collaborative, individualized, and evidence-based approaches reporting good outcomes. Specific occupational therapy interventions are suggested to delineate our role with this high-risk population during transition to independent living: both novel interventions and additions to current evidence-based programming.